THE EFFECT AROMATHERAPY CAJUPUT OIL CONCERNING EMESIS GRAVIDARUM ON PREGNANT WOMEN TRIMESTER 1 IN INDEPENDENT MIDWIFE’S CLINIC NY F PONOROGO - Rindang Fitriana Ulfa; Sri Haryuni; Ediatmi Ediatmi (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2018)
Emesis Gravidarum can be very disturbing activity and impact on the maternal and fetalmaternal obstacles. The incidence of emesis gravidarum in the world is 70-80% of thenumber of pregnant women, one non-pharmacological method that can reduce the intensityof nausea vomiting by cajuput oil.The purpose of this study was to determine whether there is an influence of aromatherapycajuput oil on emesis gravidarum in pregnant women trimester 1 in clinic Ny F PonorogoCity Year 2015This research is survey research with cross sectional approach. Population in thisresearch is trimester 1 pregnant woman at clinic Ny F city of Ponorogo year 2015 whichamounted to 17 pregnant women taken by using total sampling. The data were analyzed byunivariate analysis with independent variable frequency distribution and dependent andbivariate analysis using Wilcoxon sign rank test.P-value value: 0.000 and alpha 0.005 Statistical test results show that cajuput oil has asignificant effect on emesis gravidarum intensity.It can be concluded that there is an effect of Aromatherapy cajuput oil onemesisgravidarum in trimester 1 pregnant woman, so it is expected that cajuput oil can beone of alternative non pharmacological method that can help to reduce the intensity ofemesis gravidarum